Status epilepticus in sub-Saharan Africa: New findings. - Newton, C; Kariuki, S (2013)
Status epilepticus (SE) is common in sub-Saharan Africa, particularly in children. Most cases in children are caused by infections, particularly malaria in endemic areas. The outcome is worse than in the West, probably because of delays in initiating treatment, and lack of skills and facilities for the management of SE. However some of the causes, for example, falciparum malaria, offer challenges in the diagnosis and the treatment of SE. Exposure to falciparum malaria increases the risk of SE. Much of the SE in Africa could be prevented by reducing the incidence of infections. The outcome could be improved through education, development of locally appropriate guidelines, and provision of appropriate facilities.